A yield-vertex modification of two-surface models of metal plasticity - Petryk, H.; Thermann, K. (Archives of Mechanics, 1997)
A phenomenological model of elastoplastic behaviour of metal polycrystals is proposed which combines the features of micromechanical models with the classical flow theory of plasticity. The standard equation of a smooth loading surface describes here an outer limit surface which is never reached. The actual inner yield surface possesses a vertex at the current loading point, interpreted as the point of intersection of active yield surfaces for plastic flow mechanisms at a micro-level. The incremental response of the material at the vertex is defined in terms of the position of the current stress relative to the outer surface. In the computational version of the model, the effects of partial unloading and of physical and constraint hardening are represented by separate constitutive functions.